Adolescents' future orientation and nonmedical use of prescription drugs. (February 2017) - Steiger, Rena M.; Stoddard, Sarah A.; Pierce, Jennifer
Abstract: Introduction: How adolescents think about their future (i.e., future orientation) impacts their risk-taking behavior. The purpose of the present analysis was to explore whether future orientation (future planning, perceived risk to future goals, and positive future expectations) was associated with nonmedical use of stimulants and analgesics in a sample of high school students. Methods: Information on future orientation and nonmedical use of prescription drugs (NMUPD) were collected using a paper-and-pencil survey from a sample of 9th–12th grade students in a Midwestern school. Results: Higher perceived risk to future goals and positive future expectations were associated with a lower likelihood of self-reported nonmedical use of stimulants (n = 250; OR = 0.46, 95% CI: 0.26, 0.83; OR = 0.15, 95% CI: 0.05, 0.47, respectively). Only higher perceived risk to future goals was associated with a lower likelihood of self-reported nonmedical use of analgesics (n = 250; OR = 0.40, 95% CI: 0.24, 0.68). In a follow-up analysis limited to students who endorsed alcohol or marijuana use, perceived risk to future goals remained associated with a lower likelihood of nonmedical use of stimulants and analgesics. Conclusions: Results suggest that risk perception might be a salient protective factor against both nonmedical use of stimulants and analgesics. Overall, the differential impact of conceptualizations of future orientation might depend on the class of prescription drug used, demonstrating a need to consider prescription drugs individually in the development of future studies and interventions. Highlights: Future orientation might play a role in adolescents' NMUPD. Perceived risk to future goals was associated with a lower likelihood of NMUPD. Education about the risks of NMUPD shows potential for future intervention work.